PENDIDIKAN INKLUSIF BERBASIS WELL-BEING PESERTA DIDIK: TINJAUAN LITERATUR TERHADAP STRATEGI PEMBELAJARAN BERMAKNA BAGI ANAK BERKEBUTUHAN KHUSUS - Takdir, Sindy; Wiwin Setiani; Masriah; Irmiani; Sai Handari; Lina Revilla malik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education strives to offer all kids, particularly those with special needs, fair chances to learn. However, limited teacher preparation, subpar curriculum changes, and a lack of social support are still obstacles in many inclusive early childhood education settings when it comes to developing learning experiences that promote student well-being. The purpose of this research is to investigate the correlation between student well-being, inclusive education, and effective learning strategies for young children with special needs. By examining academic journals issued between 2021 and 2025 using databases such Google Scholar, Scopus, ERIC, ScienceDirect, SpringerLink, and Garuda, the study used a literature review approach. Content analysis was used to analyze data in order to determine significant themes, similarities, differences, and implications throughout studies. The findings demonstrate that student well-being is a core element of effective inclusive education and is strongly correlated with feelings of security, social acceptance, engagement in learning, and positive connections with classmates and teachers. Children with special needs were shown to have increased learning engagement and psychological health when they used creative learning methods like play-based activities, direct experiences, exploration, and good social interactions. Inclusive educational achievement is greatly helped by supportive learning environments and close cooperation between teachers, parents, and experts. The research finds that incorporating important learning, social support, and well-being ideas is critical for creating inclusive early childhood education that promotes holistic child development. Keywords: Inclusive Education, Student Well-Being, Meaningful Learning, Children with Special Needs, Early Childhood Education.